Experience of municipal waste processing in EU - Hulevatа, Iryna; Salavor, Oksana; Nychyk, Oksana; Bublienko, Natalia (My University, 2022)
The theses analyze various ways of processing household waste in the countries of the European Union. In recent years, the countries of Western Europe have gained considerable successful experience in the disposal of household waste. This experience can be useful for the countries of Eastern Europe. У тезах проаналізовані різні способи переробки побутових відходів у країнах Європейського Союзу. За останні роки країни Західної Європи набули значного успішного досвіду утилізації побутових відходів. Цей досвід може бути корисним для країн Східної Європи.
Keywords: кафедра екології та екоменеджменту; European Union; municipal waste; disposal; Європейський Союз; комунальні відходи; утилізація